Integration Green Accounting and Firm Value on Financial Performance - Etty Harya Ningsi; Manurung, Lambok; Lubis, Irna Triannur; Widodo, Slamet (Pusat Penerbitan dan Publikasi Ilmiah, FEB, Universitas Muslim Indonesia, 2024)
Effective green accounting practices can improve a company's image in the eyes of consumers and investors, which in turn can influence company value. Additionally, positive perceptions of firm value can result in lower costs of capital and better access to financial resources, which can ultimately strengthen financial performance. This research aims to determine the effect of the integration of green accounting and firm value on financial performance. This research analyzes manufacturing companies listed on the Indonesia Stock Exchange in 2021-2023. The type of research used is quantitative research. The data used is secondary data from the company's annual report. The sample in this research was 35 manufacturing companies listed on the Indonesia Stock Exchange consecutively in 2021-2023. The sampling technique in this research used purposive sampling. The data analysis technique used is path analysis using the eviews 10 program. The research results show that green accounting has no effect on financial performance, firm value has a positive effect on financial performance, and green accounting and firm value have a positive effect on financial performance. Therefore, by integrating green accounting and corporate value in financial performance analysis, companies can gain a more holistic understanding of their environmental impact, investor perceptions, and overall financial health. This can help them identify opportunities to increase efficiency, minimize environmental risks and create long-term, sustainable value for all stakeholders.